Echinoid associations with coral habitats differ with taxon in the deep sea and the influence of other echinoids, depth, and fishing history on their distribution. (March 2018) - Stevenson, Angela; Davies, Jaime S.; Williams, Alan; Althaus, Franziska; Rowden, Ashley A.; Bowden, David A.; Clark, Malcolm R.; Mitchell, Fraser J.G.
Abstract: Patterns of habitat use by animals and knowledge of the environmental factors affecting these spatial patterns are important for understanding the structure and dynamics of ecological communities. Both aspects are poorly known for deep-sea habitats. The present study investigates echinoid distributions within cold water coral (CWC) habitats on continental margins off France, Australia, and New Zealand. It further examines the influence of habitat-related variables that might help explain the observed distribution of echinoid taxa. Six echinoid taxa were examined from video and photographic transects to reveal taxon-specific distribution patterns and habitat-related influences. The Echinoidea were found in all habitats studied, but tended to aggregate in architecturally complex habitats associated with living cold-water corals. However, a taxon-specific investigation found that such associations were largely an artefact of the dominant taxa observed in a specific region. Despite the food and shelter resources offered to echinoids by matrix-forming coral habitats, not all taxa were associated with these habitats, and some had a random association with the habitats examined, while others displayed non-random associations. Echinoid distribution was correlated with several variables; the presence of other echinoids, depth, and fishing history were the most influential factors. This study indicates that image data can be a useful tool to detect trends in echinoid habitat associations. It also suggests that refinement of the methods, in particular with studies conducted at a more precise taxon and habitat scale, would facilitate better quantitative analyses of habitat associations and paint a more realistic picture of a population's ecology. Most deep-sea ecological studies to date have been conducted at a relatively coarse taxonomic and habitat resolution, and lack sufficient resolution to provide useful information for the conservation of vulnerable deep-sea habitats. Highlights: Group Echinoidea and taxon-specific habitat associations in a region differ. Not all taxa associate with matrix-forming coral habitats, some are random and not. Distribution correlated with presence of other echinoids, depth, and fishing history. Image data can be a useful tool to detect trends in echinoid habitat associations. Precise taxon and habitat scale paint a more realistic picture of a pop. ecology.